Language input, learning environment, and motivation of a successful EFL learner - Arif Nugroho; M. Rizal Akbar Zamzami; Nur Farah Ukhrowiyah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
The present study involved one EFL learner who was regarded as successful, not only of understanding second language acquisition theories but also of demonstrating exceptional language skills thus far. An in-depth semi-structured interview was administered with three key objectives – to identify features of language inputs that enable her to develop English skills, to investigate her situation of the learning environment, and to reveal her motivation in learning the language. The participant was a successful EFL learner who was determined by the excellent TOEFL score and performed an outstanding achievement in English proven by the academic transcript. The data were gathered by means of a semi-structured interview and analyzed through the transcription process, coding, and drawing the conclusion. The results indicated that joining an intensive class and integrating English in her daily activities had primarily contributed to her language skill improvement. While the physical environment slightly provided a conducive environment for learning English, her academic environment was steadily supporting her. In addition to the importance of English in her future, the participant was successful in keeping her motivation to learn the language. These findings could contribute to a better understanding of how Indonesian EFL learners successfully acquire a foreign language.